Correlation of Gleason Scores with Diffusion-Weighted Imaging Findings of Prostate Cancer - Rajakumar Nagarajan; Daniel Margolis; Steven Raman; Ke Sheng; Christopher King; Robert Reiter; M. Albert Thomas (Advances in Urology)
The purpose of our study was to compare the apparent diffusion coefficient (ADC) derived from diffusion-weighted imaging (DWI) of prostate cancer (PCa) patients with three classes of pathological Gleason scores (GS). Patients whose GS met these criteria (GS 3+3, GS 3+4, and GS 4+3) were included in this study. The DWI was performed using 𝑏 values of 0, 50, and 400 s/mm2 in 44 patients using an endorectal coil on a 1.5T MRI scanner. The apparent diffusion coefficient (ADC) values were calculated from the DWI data of patients with three different Gleason scores. In patients with a high-grade Gleason score (4+3), the ADC values were lower in the peripheral gland tissue, pathologically determined as tumor compared to low grade (3+3 and 3+4). The mean and standard deviation of the ADC values for patients with GS 3+3, GS 3+4, and GS 4+3 were 1.135±0.119, 0.976±0.103 and 0.831±0.087 mm2/sec. The ADC values were statistically significant (𝑃<0.05) between the three different scores with a trend of decreasing ADC values with increasing Gleason scores by one-way ANOVA method. This study shows that the DWI-derived ADC values may help differentiate aggressive from low-grade PCa.